Une perspective décentrée sur l’apprentissage en situation de travail : les conditions d’exercice des personnes formatrices en entreprise - Nadia Lamamra; Barbara Duc (Éducation et Socialisation)
The article focuses on learning in the workplace from the perspective of the conditions of practice of the people training in a company. The aim is to question the feasibility of on-the-job training in a productive organization. Based on semi-structured interviews conducted in the French-speaking part of Switzerland with people in charge of training apprentices, as well as in situ observations, the article concentrates on the constraints experienced and their impact on the daily training process. The results look at the prescribed activity, but also at the different manifestations of reality. They underline the primacy of production in the different organizational settings. In addition, they reveal modalities of on-the-job training, which could be described as paradoxical. Finally, the discussion questions the tension between production and training from the perspective of the discrepancy between prescribed and real.